2016
DOI: 10.1038/srep33083
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Supplementation for Patients with Dry Eye Syndrome Refractory to Conventional Treatment

Abstract: This study investigated the effect of vitamin D supplementation in patients with dry eye syndrome (DES) refractory to conventional treatment with vitamin D deficiency. A total of 105 patients with DES refractory to conventional treatment and vitamin D deficiency that was treated with an intramuscular injection of cholecalciferol (200,000 IU). Serum 25-hydroxyvitamin D (25(OH)D) levels were measured. Eye discomfort was assessed using ocular surface disease index (OSDI) and visual analogue pain score (VAS). Tear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 47 publications
4
51
0
1
Order By: Relevance
“…These observations are clinically relevant because oral vitamin D supplementation is being explored in DED management, which shows favorable outcomes by enhancing the efficacy of topical treatment and improving various DED signs and symptoms, particularly in those with vitamin D deficiency or those refractory to conventional treatment. [75][76][77] To summarize, an imbalance in nociception modulators with an increase in pronociceptive factors and a decrease in antinociceptive factors was observed ( Fig. 7) to be significantly associated with signs and symptoms in DED patients.…”
Section: Tear Factors Associated With Dry Eye Signs and Symptomsmentioning
confidence: 78%
“…These observations are clinically relevant because oral vitamin D supplementation is being explored in DED management, which shows favorable outcomes by enhancing the efficacy of topical treatment and improving various DED signs and symptoms, particularly in those with vitamin D deficiency or those refractory to conventional treatment. [75][76][77] To summarize, an imbalance in nociception modulators with an increase in pronociceptive factors and a decrease in antinociceptive factors was observed ( Fig. 7) to be significantly associated with signs and symptoms in DED patients.…”
Section: Tear Factors Associated With Dry Eye Signs and Symptomsmentioning
confidence: 78%
“…Starting from these assumptions, vitamin D has been investigated as a potential therapy for DED. Bae and co-authors evaluated the efficacy of vitamin D supplementation in patients with DED refractory to conventional treatment who presented vitamin D deficiency, and reported a significant improvement of Schirmer test, break-up time, corneal staining, eyelid margin hyperemia and subjective discomfort symptoms [91]. In agreement with these results, Yang and co-workers observed a significant improvement of dry eye symptoms and corneal staining after 2 months of vitamin D supplementation [92] Furthermore, the therapeutic effect of tear substitutes depends on serum vitamin D levels, and oral supplementation has shown to synergistically enhance their efficacy [93].…”
Section: Vitamin Dmentioning
confidence: 99%
“…Meng YF, et al have also reported that Serum 25(OH) levels were significantly lower in DES subjects of their study [19.3+/-5.8 ng/ml] as compared to their control subjects [31.6+/-7.3], which was statistically significant, p-value <0.001[13]. Seok Hyun Bae, et al also found deficient levels of Vitamin D [10.52+/-4.61] in DES subjects of their study group[16].…”
mentioning
confidence: 63%